ASSISTANCE IN THE USE OF THE TNDE APPLICATION FOR SUPPORTING HUMAN RESOURCES MANAGEMENT AT PT. ANGKASA PURA I - Winda Maharani, Ni Putu Ratih; Putri, Putu Indah Dianti; Dharmayasa, I Gusti Ngurah Putu (LPPM Univ. Ibn Khaldun Bogor, 2023)
This study focuses on the application of Digital Navigation Technology (TNDE) in human resource management at PT. Angkasa Pura I. The main goal is to analyze the effectiveness and efficiency of TNDE in human resource management processes. The research shows that TNDE has significant implications for improving the efficiency and effectiveness of human resource management in PT. Angkasa Pura I. The study also highlights the importance of addressing the challenges faced in implementing TNDE, such as resistance to technology. Interaction between TNDE and aplikasi is crucial for efficient problem-solving and effective learning. The research recommends implementing TNDE programs, improving communication between TNDE and TNDE, and optimizing TNDE implementation to align with the needs of TNDE and technology development.